Efficacy of sequential use of telbivudine in hepatitis B e antigen‐positive chronic hepatitis B patients with partial responses to pegylated interferon: a pilot study. (4th March 2013) - Huang, Z.; Zhao, Z.; Zheng, Y.; Peng, L.; Lin, C.; Deng, H.; Gao, Z.
Summary: The aim of this study was to investigate the efficacy of sequential use of telbivudine in hepatitis B e antigen (HBeAg)‐positive chronic hepatitis B patients with partial responses to pegylated interferon. Patients with partial responses to 48 weeks of pegylated interferon treatment were divided into two groups. In group A, patients stopped pegylated interferon directly without sequential treatment. In group B, patients received sequential treatment with telbivudine 600 mg/day. HBeAg, HBeAb, hepatitis B virus (HBV) DNA, alanine aminotransferase (ALT) and creatine kinase levels were determined at baseline and at weeks 12, 24, 36 and 48. Responses and safety were assessed after 48 weeks of telbivudine treatment. Thirty‐six patients were recruited. Eighteen of these patients stopped pegylated interferon without sequential treatment (group A). After 48 weeks of follow‐up, five patients (28%) had undergone HBeAg seroconversion, nine patients (50%) had undetectable levels of HBV DNA, and 11 patients (61%) achieved normal alanine aminotransferase (ALT) levels. The other 18 patients received sequential telbivudine treatment (group B). After 48 weeks of treatment, 11 patients (61%) had undergone HBeAg seroconversion, and all patients had undetectable levels of HBV DNA and normal ALT levels. All patients tolerated sequential telbivudine treatment, and only slightly elevated creatine kinase levels were observed. Switching to telbivudine therapy was efficient and safe in HBeAg‐positive chronic hepatitis B patients with partial responses to 48 weeks of pegylated interferon. Sequential treatment with telbivudine resulted in an HBeAg seroconversion rate of 61% and an HBV DNA loss rate of 100% after 48 weeks. This promising strategy warrants further investigation.